6시그마 성공요인과 혁신역량이 혁신성과에 미치는 영향 - 이용건; 류태수; Lee, Yong Keon; Ryu, Tae Soo (品質經營學會誌, 2014)
Purpose: The purpose of this paper is to identify Six Sigma success factors and analyse the effects of Six Sigma success factors and innovation capability on innovation performance. Methods: The study build a research framework which include the variables of Six Sigma success factors, innovation capability, and innovation performance. A sample of 127 survey questionnaires is taken to test the proposal theoretical model through structural equations modeling using AMOS 20.0. Results: This study proves that there are the positive relationship between Six Sigma success factors, innovation capability, and innovation performance. It also confirms that there are the partial mediating effects of innovation capability between Six Sigma success factors and innovation performance. Conclusion: There are various factors affecting innovation performance of firms. This study provide the mechanism transformed from Sig Sigma to innovation performance.